2020
DOI: 10.1155/2020/6510439
|View full text |Cite
|
Sign up to set email alerts
|

Damage Evaluation of the Paving around Manholes under Vehicle Dynamic Load

Abstract: It is very important for pavement engineers to know which factors are the main reasons for the damage of the paving around manholes. Based on the investigation on the damage of paving around manholes, a vibration model with multidegree of freedom for the vehicle-manhole cover was established and analyzed. After that, the Matlab software was used to obtain the variation law of impact load over time, and the 95% fourth power of the aggregate force was used as the index to evaluate the pavement damage. Finally, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This method requires a unified processing and analysis of various influencing factors, calculating their relation and sorting them according to the magnitude of the relation to identify the main influencing factors [51]. Many scholars have applied this method to different fields [52][53][54]. It is suitable for analyzing and evaluating the influencing factors of mid-span peak displacement of RC columns.…”
Section: Grey Relation Analysis Methodsmentioning
confidence: 99%
“…This method requires a unified processing and analysis of various influencing factors, calculating their relation and sorting them according to the magnitude of the relation to identify the main influencing factors [51]. Many scholars have applied this method to different fields [52][53][54]. It is suitable for analyzing and evaluating the influencing factors of mid-span peak displacement of RC columns.…”
Section: Grey Relation Analysis Methodsmentioning
confidence: 99%
“…where, d i,j are the percentage of dynamic loads; Q j are dynamic loads (kips); and s k are the percentage of number of axles with static load Q k determined from WIM data. It was assumed that dynamic loads can be characterized as normal distribution with the average value in the middle of a given interval and standard deviation, which has been proved and applied in previous works [6,13]. The DLC values in the formula would change with pavement roughness levels and axle load intervals designated by MEPDG.…”
Section: Dynamic Axle Load Spectramentioning
confidence: 99%
“…Gillespie et al introduced the distribution of dynamic loads under the wheel with a mean value equal to static load and a standard deviation, which follows normal distribution [5]. Hu et al evaluated the pavement damage around manholes and suggested that the maximum of dynamic load was 1.29 times that of the static load, which increased the pavement damage coefficient up to 2.12 times that of the static load [6]. To investigate the impact of dynamic loads on pavement surface conditions, the dynamic loading coefficient (DLC) was defined as a ratio by dividing the standard deviation of dynamic loads by the mean value.…”
Section: Introductionmentioning
confidence: 99%
“…They will also appear at the sewer junction for easy servicing access (Ayasrah, 2020). Manholes are very important because it is the only way to access sewer for maintenance and to do an inspection (Hu et al, 2020). If the manhole cover is damaged, it should be replaced immediately as the gases it contains are hazardous to human health and safety.…”
Section: Characteristics Of Manholementioning
confidence: 99%